Uji Organoleptik Dan Sifat Kimia Kue Semprong Campuran Tepung Ubi Jalar Ungu (Ipomoea batatas) Dan Tepung Terigu - Olfita S Montolalu; Tineke Langi; Teltje Koapaha (Universitas Sam Ratulangi, 2019)
Sweet potato as a food ingredient, has a good quality in terms of nutritional content, especially carbohydrates, minerals, and vitamins. Processing purple sweet potato into flour is one way to store and preserve purple sweet potato.